2022
DOI: 10.2147/ijgm.s346335
|View full text |Cite
|
Sign up to set email alerts
|

Low ZCCHC9 Gene Expression in Peripheral Blood May Be an Acute Myocardial Infarction Genetic Molecular Marker in Patients with Stable Coronary Atherosclerotic Disease

Abstract: Purpose ZCCHC9 is a zinc finger protein with a CCHC zinc finger structure and has important roles in several cellular processes. This study was conducted on an expanded number of samples to evaluate The usefulness of ZCCHC9 gene expression in peripheral blood as a molecular marker for the prediction of AMI (acute myocardial infarction) risk. Patients and Methods Peripheral blood samples were collected from 117 patients with stable CAD (coronary atherosclerotic disease) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The expression level of the adior2 gene, for example, is linked to the advancement of coronary atherosclerosis [ 70 ]. Meng et al revealed that numb ABCB1, ACSL1, ZHHC9, and other genes have important roles in the pathogenesis of atherosclerosis [ 71 , 72 , 73 , 74 ]. Furthermore, a study from the University of Washington discovered that the SVEP1 gene causes atherosclerosis in the absence of cholesterol [ 75 ].…”
Section: Gene and Protein Markersmentioning
confidence: 99%
“…The expression level of the adior2 gene, for example, is linked to the advancement of coronary atherosclerosis [ 70 ]. Meng et al revealed that numb ABCB1, ACSL1, ZHHC9, and other genes have important roles in the pathogenesis of atherosclerosis [ 71 , 72 , 73 , 74 ]. Furthermore, a study from the University of Washington discovered that the SVEP1 gene causes atherosclerosis in the absence of cholesterol [ 75 ].…”
Section: Gene and Protein Markersmentioning
confidence: 99%